2000
DOI: 10.1002/1097-4636(20010305)54:3<400::aid-jbm130>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of A-P translation and rotation on the wear of UHMWPE in a total knee joint simulator

Abstract: We developed a three-channel total knee joint simulator and studied the effect of tibial anterior-posterior translation and internal/external rotation on the wear of polyethylene tibial inserts in total knee replacements (Anatomic Graduated Component knees). The wear rate was the lowest in experiment (Exp.) 1, without translation and rotation [1.74 mg/million (mg/Mc) cycles]. In Exp. 2, with +/-5 degrees tibial rotation added, the wear rate increased to 10.6 mg/Mc. In Exp. 3, with rotation and -12 mm tibial tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Several factors that influence wear such as implant design, manufacturing, sterilization method, joint lubrication, patient weight, and activity level have been studied (Schmalzried et al, 1999). Wear is also highly dependent on kinematics; increased AP translation (anterior-posterior translation) and IE rotation (internal-external rotation) have been reported to raise PE wear in TKR (Kawanabe et al, 2001;McEwen et al, 2005). The motion of the natural knee is governed by active forces that originate from the muscles as well as dynamic and gravitational forces (Mikosz et al, 1988;Morrison, 1970).…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Several factors that influence wear such as implant design, manufacturing, sterilization method, joint lubrication, patient weight, and activity level have been studied (Schmalzried et al, 1999). Wear is also highly dependent on kinematics; increased AP translation (anterior-posterior translation) and IE rotation (internal-external rotation) have been reported to raise PE wear in TKR (Kawanabe et al, 2001;McEwen et al, 2005). The motion of the natural knee is governed by active forces that originate from the muscles as well as dynamic and gravitational forces (Mikosz et al, 1988;Morrison, 1970).…”
Section: Introductionsupporting
confidence: 48%
“…Additionally implant kinematics are important. Higher AP translation and IE rotation have been shown to increase PE wear in TKR (Kawanabe et al, 2001). In the absence of the ACL, AP translation increased by 38%, IE rotation by 47% and the PE wear rate by 40% in our study.…”
Section: Discussionmentioning
confidence: 93%
“…Kawanabe et al (2001) and McEwen et al (2005) have shown experimentally that changes in the magnitude of translation and/or rotation can substantially impact measured wear. McEwen et al (2005) quantified a four-fold reduction in wear when the kinematics were scaled from 0-10 mm (AP) and 751 (IE) to 0-5 mm and 72.51.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have quantified the importance of kinematic conditions (Blunn et al, 1991;Kawanabe et al, 2001;McEwen et al, 2005;Schwenke et al, 2005) and contact pressure and area (Mazzucco and Spector, 2003;Sathasivam et al, 2001) on wear. Kawanabe et al (2001) measured a 6-11 fold increase in wear rates with the addition of internal-external (IE) rotation and anterior-posterior (AP) translation when compared to wear rates with only flexion and axial load profiles. A 50% reduction in kinematic inputs similarly resulted in a four-fold wear reduction in TKR simulator testing (McEwen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…119 However, it is known from both physical laboratory testing and finite element analysis that load magnitude in combination with displacement are factors influencing UHMWPE damage. [120][121][122][123][124][125][126][127] While a recommendation for patient weight loss before surgery may be justified from these laboratory investigations, the clinical reality of achieving this does not lie in the patient's or surgeon's favor. 128…”
Section: Patient Factors: Do They Really Matter?mentioning
confidence: 99%